University Students Dealing with Sexually Transmitted Infections and HIV/AIDS: Knowledge and Practice, a Cross-sectional study Conducted in Fianarantsoa, Madagascar - A.J. Andriamamonjisoa; R. Rakotomalala; V. Andriananja; M. Raberahona; F. Randriamampionona; R.L. Andrianasolo; M.J.D. Randria; R.A. Rakotoarivelo (European Scientific Journal, ESJ, 2022)
This study aimed to evaluate the Knowledge and attitude of the academic students about sexually transmitted infections and HIV at the university of Fianarantsoa in 2018.Materials and methods: This was an analytical cross-sectional study conducted among undergraduate students at the University Andrainjato-Fianarantsoa. Knowledge was assessed using a score where each correct answer was given one point.Results: 1035 students were included, 67.7% (n=701) had good knowledge about STIs, and HIV/AIDS. Sexual transmission (83.9%; n=868) was the most known. On multivariate analysis, being a student at the faculty of medicine (p<0.001, aOR 137.3 [19.1-988]), faculty of Letters (p<0.001, aOR 4.5 [2.8-7.2)]), or the Normal Graduate School (NGS) (p<0.001, aOR 6.7 [3.3-13.7]), being tested for HIV before (p= 0.002, aOR 1.6 [1.2-2.2]) constitute the major factor of good knowledge about the sexual infections. The majority (71.8%, n=743) have had sexual intercourse before, and the median age of first sexual activities was 18 years (17-20). The use of Condoms (44.4%, n=460) was the most practiced in the STIs prevention method, followed by fidelity (19.8%; n=205) and abstinence (11.4%, n=118). Among the students, 29.3% (302) had high-risk sexual behavior in the last 3 months.Conclusion: The proportion of academic students with good knowledge of STIs and HIV is not satisfactory. There was a discordance between the knowledge of STI prevention and the daily university practice of the students.